A public key-based encryption and signature verification model for secured image transmission in network. (23rd August 2019) - Jayanthi, R.; Singh, K. John
Image transmission is a challenging task due to the large file size and the security issues. Many existing systems on medical image transmission use symmetric key cryptography where the key is shared to multiple recipients leading to security leakage. This has been addressed by applying public key encryption schemes. However, a secured communication technique which uses compression, user authentication and encryption/decryption is more powerful than the existing systems on medical image transmission. Therefore, a new secured transmission algorithm which performs compression using singular value decomposition (SVD), user authentication using digital signatures and encryption/decryption using AES and RSA algorithms for image encryption and Hill-Cipher for data encryption which are coordinated using intelligent agents for communication and rules for decision making is proposed in this paper. The major advantages of the proposed model include fast transmission, increase in security and non-loss compression and decompression and intelligent decision making on medical image transmission.